Thermal Behaviour of Copper(II) Complexes of Haloaspirinates - Tarulli, Susana H. (2000)
Complexes of Cu(II) with substituted o-acetoxy benzoic acids (5-haloaspirines, X-asp) with and without pyridine (py), of composition [Cu₂(X-asp)₄] and [Cu(X-asp)₂(py)₂] have been synthesized and characterized. Electronic and vibrational spectroscopic data of these complexes are reported. Its thermal behaviour was investigated by thermogravimetry and differential thermal analysis. In all complexes, the haloaspirinate ligands decompose in two or three steps, starting with the break up of the coordinated acetoxy groups. CuO is obtained as the final pyrolysis residue in all cases.